(untitled) - Chen C. H. (Boca Raton, 2008)
Signal and Image Processing for Remote Sensing, published by Taylor and Francis in 2006, has been reissued as two volumes, this one containing the material on signal processing, and the other the material on image processing. Most of the literature on remote sensing deals with images, and only recently have developments in signal processing generally been applied to the signal processing aspects of remote sensing, as applied for example to data from microwave and geophysical sensors. Electronic and computer engineers and other technical contributors here describe the current status of the technology and theory.
Keywords: Remote sensing,Signal processing,Kỹ nghệ quang học; Data processing